Regionally surgical resection of stage-IV adenocarcinoma acquired tyrosine kinases inhibitor-resistance - Yang, Minglei; Zheng, Enkuo; Xu, Xiang; Ni, Junjun; Li, Junfang; Zhao, Guofang (Journal of Thoracic Disease, 2019)
A 65-year-old male presented with a mass at left lower lobe (LLL) in November 2010, without a history of smoking. Computer tomography (CT) and positron emission tomography (PET)-CT scans showed a 41 mm × 38 mm solid mass at LLL with small nodules interspersed in both lungs. The largest nodule had a maximum diameter of about 12 mm at left upper lobe (LUL) and was considered to be a metastasis according to fludeoxyglucose (FDG)-PET result. The biopsy guided by CT pathologically confirmed lung adenocarcinoma of the primary lesion.